MG-leach: an enhanced leach protocol for wireless sensor network - Hicham Ouldzira; Hajar Lagraini; Ahmed Mouhsen; Mostafa Chhiba; Abdelmoumen Tabyaoui (International Journal of Electrical and Computer Engineering (IJECE), 2019)
A wireless sensor network is made up of a large number of small sensor nodes with limited energy resources, which is a real problem for this network. In this article, we will study the ingestion of node energy in these networks at the routing level. In addition, we are modifying one of the most popular routing algorithms for data communication in the WSN: LEACH (Adaptive Hierarchy with Low Power Consumption). The modified version of the LEACH base version "MG_LEACH" uses an intermediate cluster header to transmit data, extend the network lifetime and send more data than the original protocol. Our proposed algorithm is simulated using MATLAB to verify the effectiveness of improving the lifetime of this network. The results of the simulation confirmed that the system was working better than the LEACH basic system and that the network life had been improved.